Zero discharge treatment technology of palm oil mill effluent - Muzzammil Ngatiman (2020)
Palm oil processing operation is invariably accompanied by palm oil mill effluent (POME) considered to be an environmental pollutant. While anaerobic digestion and the present tertiary treatment technologies of POME are able to meet the current regulatory effluent discharge requirement of biological oxygen demand (BOD) 100 mg litre-1 – the current limit set by the Department of Environment (DOE) – the existing technologies are unable to consistently meet the proposed stringent BOD regulatory requirement of 20 mg litre-1 to be imposed by the DOE. This article investigates the possibility of integrating several bioprocesses for POME treatment at the Malaysian palm oil mills by transforming the POME into several high valueadded products; with BOD 20 mg litre-1 attainable at its final discharge. This integrated approach has the potential of achieving zero-effluent discharge along with the production of biogas, biofertiliser and recycled water, in treating industrial wastewater to reduce pollution.